2001
DOI: 10.1103/physrevb.63.224417
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of theS=1/2antiferromagnetic zig-zag ladder with anisotropy

Abstract: The spin-1/2 antiferromagnetic zig-zag ladder is studied by exact diagonalization of small systems in the regime of weak inter-chain coupling. A gapless phase with quasi long-range spiral correlations has been predicted to occur in this regime if easy-plane (XY ) anisotropy is present. We find in general that the finite zig-zag ladder shows three phases: a gapless collinear phase, a dimer phase and a spiral phase. We study the level crossings of the spectrum, the dimer correlation function, the structure facto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…In this doubly degenerate phase a nonzero spin current polarized along the easy axis flows along the ladder, and the transverse spin-spin correlations are incommensurate and may even decay algebraically within some parameter range, as it is the case at the XX point. This picture is supported by recent numerical simulations 11,12,13,14 . In particular, the numerical work by Hikihara et al 11,12 has indeed confirmed the existence of the critical spin-nematic phase in a broad region of the phase diagram for spin-anisotropic chains, both for integer and half-integer spins.…”
Section: Introductionsupporting
confidence: 69%
“…In this doubly degenerate phase a nonzero spin current polarized along the easy axis flows along the ladder, and the transverse spin-spin correlations are incommensurate and may even decay algebraically within some parameter range, as it is the case at the XX point. This picture is supported by recent numerical simulations 11,12,13,14 . In particular, the numerical work by Hikihara et al 11,12 has indeed confirmed the existence of the critical spin-nematic phase in a broad region of the phase diagram for spin-anisotropic chains, both for integer and half-integer spins.…”
Section: Introductionsupporting
confidence: 69%
“…Conversely, exact diagonalization studies find a finite Drude weight in the gapless phase of the frustrated spin-1/2 chain at zero temperature. 74,75,90 In the low, or more extremely, zero temperature case, effective low-energy theories are expected to give a valid description, which typically predict diverging transport coefficients of clean spin systems (see, e.g., Ref. 91).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Also, recently an analysis of the exact properties of such finite systems was carried out, looking at various correlation functions and the structure of the spectrum both in the isotropic and the anisotropic cases [32]. The spin stiffness of the zig-zag ladder was calculated, and it was found evidence for a gapless regime at weak coupling that survives the thermodynamic limit in the case of XY anisotropy.…”
Section: Hamiltonianmentioning
confidence: 99%